Simulation Study on Mechanical Characteristics of Rock Bolt in Rock Mass with Bedding Separation Based on the Nonlinear Bond Slip Relationship - Ning Li; Zhigang Du; Fuqiang Gao; Fuzhou Qi; Haiping Gao; Mingxia Li; Xiaoqiang Wang (Geofluids)
The mechanical equation on the mechanical characteristics of rock bolt in rock mass with bedding separation is established, based on the bond slip relationship of anchoring interface by the load transfer method. The validity of the numerical simulation is verified by the analytical solution of mechanical equation, when the bond slip relationship is linear. Further, the nonlinear bond slip relationship of anchoring interface is input into Flac3D by FISH. The mechanical characteristics of rock bolt are studied with the single and multiple bedding separation by numerical simulation. The results show that the axial force and the interfacial shear stress distribution curves on both sides are symmetrically distributed with the single bedding separation in rock mass, when the bedding separation is located in the center of the anchoring segment. When the bedding separation positions are not located in the center of the anchoring segment, the bedding separation value at different positions versus the axial force curves shows a single peak distribution. The axial force of rock bolt is mainly controlled by the side with the shorter anchoring length. Compared with the single bedding separation in rock mass, the additional stress of rock bolt occurred by the multiple bedding separation will superimpose each other. This paper leads to a better understanding for the load transfer mechanism for grouted rock bolt systems in rock mass with bedding separation and provides a reference for scientific support design and evaluation method.